2007
DOI: 10.1177/156482650702800207
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Use of Vitamin A–Fortified Vegetable Oils among Consumers of Different Socioeconomic Status in Thailand

Abstract: Fortification of vegetable oils with vitamin A for consumers of different socioeconomic status is feasible; however, light protection is needed for better stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
1
7
0
3
Order By: Relevance
“…One way of analysis of variance ( ANOVA) showed that there was significant loss of vitamin A levels in fortified sunflower oil after 35 days of sunlight exposure as compared to fortified soybean oil; 40% versus 27% (p < 0.05) respectively. The results obtained in this study for vitamin A loss in fortified soybean oil are in agreement with the finding of Puysuwan et al (2007) who noted that fortified soybeans oil in losed PET bottles exposed to sunlight for 4 weeks at room temperature reduced thr initial vitamin A concentration by 27.1 ± 12.1% without accounting for the oxygen exposure upon opening.The vitamin A losses in oils and maize flour from samples from street vendors (Table 2) could be attributed to prolonged exposure to sunlight and also the nature of the packaging material used (sachets for oils and basins for flour) by the vendors (Chakravarty,2000). This is so because packaging is also a contributing factor to the losses in Vitamin A (Oluwalana et al, 2015).…”
Section: Resultssupporting
confidence: 81%
“…One way of analysis of variance ( ANOVA) showed that there was significant loss of vitamin A levels in fortified sunflower oil after 35 days of sunlight exposure as compared to fortified soybean oil; 40% versus 27% (p < 0.05) respectively. The results obtained in this study for vitamin A loss in fortified soybean oil are in agreement with the finding of Puysuwan et al (2007) who noted that fortified soybeans oil in losed PET bottles exposed to sunlight for 4 weeks at room temperature reduced thr initial vitamin A concentration by 27.1 ± 12.1% without accounting for the oxygen exposure upon opening.The vitamin A losses in oils and maize flour from samples from street vendors (Table 2) could be attributed to prolonged exposure to sunlight and also the nature of the packaging material used (sachets for oils and basins for flour) by the vendors (Chakravarty,2000). This is so because packaging is also a contributing factor to the losses in Vitamin A (Oluwalana et al, 2015).…”
Section: Resultssupporting
confidence: 81%
“…For example, NaFeEDTA is not allowed to be used at more than 0.2 mg/kg body weight per day in children (WHO 1999). Use of appropriate packaging is another alternative for prolonging the shelf life of fortified products, such as light‐protected containers for vitamin A‐fortified cooking oil or aluminum foil‐laminated plastic bags for iron‐fortified rice (Chitpan and others 2005; Puysuwan and others 2007). However, changes in packaging normally affect the cost of the fortified products.…”
Section: Keys To Sustainable Food Fortification Programs In Developinmentioning
confidence: 99%
“…For example, fortifying cooking oil with vitamin A for bulk transportation can be done by adding vitamin A into the truck's tank before pumping in the oil. The turbulence from pumping can homogeneously mix the fortified product without the need for additional equipment (Puysuwan and others 2007). In some cases, additional equipment may be needed.…”
Section: Keys To Sustainable Food Fortification Programs In Developinmentioning
confidence: 99%
“…Salah satu strategi untuk mengat asi fenomena ini adalah dengan fortifikasi vitamin A ke dalam bahan pangan. Fortifikasi miny ak dengan vitamin A telah dicanangkan dan dilakukan di berbagai negara seperti Thailand (Puysuwan et al, 2007), Nigeria (Oni, 2012), Pakistan (Akhtar et al, 2012), Uganda (Fiedler dan Afidra, 2010), dan Indonesia (A ndarwulan et al, 2014).…”
Section: Pendahuluanunclassified
“…Retinil palmitat sendiri merupakan vit amin A yang telah mengalami esterifikasi dengan asam palmitat. Puysuwan et al (2007) mengamati retensi vitamin A dalam bentuk ester palmitat yang digunakan sebagai fortifikan dalam minyak goreng. Minyak sawit yang digunakan untuk menggoreng pada suhu 120°C selama 5 menit memiliki retensi vit amin A sekitar 96,94 hingga 97,58%, tergantung dari bahan penggorengan yang digunakan.…”
Section: Retensi Vitamin a Dan β-Karoten Pada Minyak Goreng Curahunclassified